Plan de mejoramiento de la empresa de muebles modulares spazzios en la ciudad de Quito - Troya Ontaneda, Tatiana Estívaliz (2013)
Demand in Ecuador modular furniture has recently introduced many variations; there is a tendency towards contemporary, modern and contemporary designs; tastes and preferences of customers are very different than it was 10 years ago. That is why the Spazzios Company, located in the city of Quito, is the need to make improvements in order to increase their customers and in turn secure the loyalty of these. For this reason the following plan of improvements made by an approach and refinement of the mission and vision; followed by internal analysis taking into account each and every one of the areas of the company, it was obtained as a result that the main investment to be made is the implementation of a productive area in order to meet the needs of the customers and increase company revenue. Another area that needs to be optimized is the research and development since it was shown that it has no specific activities. Similarly, an external analysis, it was evident that the timber industry has presented an increase of 25 percent annually in sales, providing an opportunity for the company was conducted. Another aspect analyzed was the market, it was determined that the company should focus on providing better advice and variety of designs to keep your current customers as potential 16 percent say that the main feature they want is the timely delivery of modular furniture. There are about 100 companies in the city of Quito dedicated to the same activity as Spazzios of which compete directly with companies such as ATU, Multiformas and Acacia; because despite having different models and design; their target market is the same as that of the company. With all of the above improvements to be made in each of the areas, one of the most important implementation of a factory, for this improvement plan an initial investment of USD 68,197.75 will be needed she was identified. Financial evaluation was conducted in three stages, which is normal with which the company works gave as net present value (NPV) of 214,300.39 and an internal rate of return (IRR) of 75.42 percent, demonstrating this the feasibility of this plan.